Shy and outgoing preservice teachers and their responses to hypothetical problem behaviors in the classroom. Issue 5 (28th May 2021) - Deng, Qizhen; Patwardhan, Irina; Rudasill, Kathleen; Trainin, Guy; Wessels, Stephanie; Torquati, Julia; Coplan, Robert J.
Abstract: The present study explored the relations among preservice teacher shyness (shy, average, outgoing) and their responses towards hypothetical children displaying classroom problem behaviours (shy/quiet, exuberant/talkative) in the classroom. Participants were 335 elementary preservice teachers attending a Midwest university in the United States. Preservice teachers completed self-reports of shyness and responded to hypothetical vignettes depicting different classroom behaviours. Among the results, shy preservice teachers reported lower self-efficacy and less tendency to use warm/supportive and social-learning strategies as compared to their more outgoing counterparts. Shy preservice teachers also had lower tendency than average teachers to refer to high-powered strategies when dealing with shy children, but more likely with exuberant children. Results are discussed in terms of the role of personality in teaching.